2010
DOI: 10.1007/s11095-010-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Prediction of Phase Separation in Hot-Melt Extruded Solid Dispersions: A Thermal, Microscopic and NMR Relaxometry Study

Abstract: This study has presented a series of novel approaches for the identification, quantification and prediction of phase separation in HME formulations. Supersaturation of drug in the polymer caused the phase separation of the aged felodipine-Eudragit E PO formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 35 publications
(49 reference statements)
4
76
0
Order By: Relevance
“…The weakness and/or a number of the drug-polymer interactions on increasing the temperature appeared, which was also observed by Marsac et al 6 No more changes were observed in the present study; however, this might be due to the limitations of the techniques adapted, which could only probe the bulk properties of the sample. 7 As demonstrated by other researchers, [7][8][9][10][11] the dispersion of the drug in the polymer may be complex, and molecular-level dispersion, nanodispersion, phase separation, and even crystalline domains may co-exist in the so-called amorphous dispersion defined by a distinctive T g intermediate of the two T g values of the two components, leaving great concerns to its physical stability. It is hypothesized that perhaps the SD prepared in the present study was not so uniform although great efforts were made to optimize the technique and formulation, 12 and perhaps more homogeneous physical state was obtained after cooking.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The weakness and/or a number of the drug-polymer interactions on increasing the temperature appeared, which was also observed by Marsac et al 6 No more changes were observed in the present study; however, this might be due to the limitations of the techniques adapted, which could only probe the bulk properties of the sample. 7 As demonstrated by other researchers, [7][8][9][10][11] the dispersion of the drug in the polymer may be complex, and molecular-level dispersion, nanodispersion, phase separation, and even crystalline domains may co-exist in the so-called amorphous dispersion defined by a distinctive T g intermediate of the two T g values of the two components, leaving great concerns to its physical stability. It is hypothesized that perhaps the SD prepared in the present study was not so uniform although great efforts were made to optimize the technique and formulation, 12 and perhaps more homogeneous physical state was obtained after cooking.…”
Section: Discussionmentioning
confidence: 96%
“…High-speed DSC, heat capacity measurements using MTDSC, solid-state NMR spectroscopy, and pair distribution function analysis are also good choices. 8,10,13,14 The authors think that the finding is of practical importance as most of the SD are not entirely molecular-level dispersions and, in this case, suitable postcooking for a short time as an alternative strategy is suggested to improve its performance. However, it should be kept in mind that although the SD remained miscible on heating for a short time, 6 heating for a long time is against.…”
Section: Discussionmentioning
confidence: 99%
“…This gives an advantage over amorphous drugs without excipients, which are always high energy and therefore highly physically unstable structures. Crystallization can be considered as a kinetically driven process depending on mobility of molecules but thermodynamic properties resulting from the drug content and its solubility in the polymer are thought to be the key parameters regarding physical stability of solid dispersions [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…The exotherm may also appear during the cooling of the melt. However, various authors have reported the T c being observed earlier then T g for physically unstable APIs [196,197].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 98%